The Orphan C2orf40 Gene is a Neuroimmune Factor in Alzheimer’s Disease - Podvin, Sonia (JSM Alzheimers Dis Relat Dement, 2016)
Expression of the orphan C2orf40 gene is associated with the aggregation of the neurofibrillary tangle-protein tau in transgenic mice, tumor suppression, the induction of senescence in CNS, and the activation of microglia and peripheral mononuclear leukocytes. This gene also encodes several secreted pro- and anti-inflammatory neuropeptide-like cytokines, suggesting they might be implicated in the inflammatory component(s) of Alzheimer’s disease (AD). Accordingly, we evaluated human AD and control brains for expression changes by RT-qPCR, Western blot, and histological changes by immunolabeling. RT-qPCR demonstrated increased cortical gene expression in AD. The molecular form of Ecrg4 detected in cortex was 8–10 kDa, which was shown previously to interact with the innate immunity receptor complex. Immunocytochemical studies showed intensely stained microglia and intravascular blood-borne monocytes within cerebral cortical white matter of AD patients. Staining was diminished within cortical neurons, except for prominent staining in neurofibrillary tangles. Choroid plexuses showed a decreasing trend. These findings support our hypothesis that c2orf40 participates in the neuroimmune response in AD.